Executive roadmap to fraud prevention and internal control : creating a culture of compliance - Biegelman, Martin T.; Bartow, Joel T., 1958- (Hoboken, N.J. : Wiley, 2012)
'How-to, authoritative guidance for creating a best-in-class fraud prevention and compliance program in any organizationNow in a Second Edition, this practical book helps corporate executives and managers understand the full ramifications of good corporate governance and compliance. It covers best practices for establishing a unit to protect the financial integrity of a business; theories and models on how and why fraud occurs in an organization; importance of strong internal controls; major compliance and corporate governance initiatives and milestones since 1985; and more. Complete coverage includes implementation guidance for a robust fraud prevention and compliance program, including sample policies, best practice examples, and a 14-point management antifraud program. Covers fraud risk assessment and prevention guidance Looks at global risk issues, including the Foreign Corrupt Practices Act (FCPA) and UK Bribery Act Examines amendments to the Federal Sentencing Guidelines for Organizational Crime Discusses Dodd-Frank Whistleblower Provisions Explores enterprise risk management key program elements Offers coverage of how fraud and compliance failures contributed to the financial crisis Includes enhanced principles for fraud data mining Presents new cases, checklists and real-world examples, expanded international coverage, and the latest technological tools Shows executives and managers what their responsibilities are regarding fraud prevention, internal controls, and compliance Provides an instructor's website, including a test bank Other titles by Biegelman: Building a World-Class Compliance Program and Foreign Corrupt Practices Act Compliance Guidebook Completely revised and updated, Executive Roadmap to Fraud Prevention and Internal Control, Second Edition is every manager's best resource for understanding all the complex issues and responsibilities associated with fraud and compliance'--
Includes bibliographical references and index.
Keywords: Corporations -- Accounting -- Corrupt practices -- United States; Corporations -- Corrupt practices -- United States; Accounting fraud -- United States